Роль Інституту ботаніки ім. М. Г. Холодного НАН України у створення Національного ботанічного саду ім. М. М. Гришка НАН України - Черевченко, Т.М.; Чувікіна, Н.В. (Український ботанічний журнал, 2011)
Освещена роль выдающихся ученых В.И. Липского и А.В. Фомина в разработке научных основ создания Ботанического сада Украинской Академии наук (ныне — Национальный ботанический сад им. Н.Н. Гришко НАН Украины) и пребывание Ботанического сада (1935— 1944) в составе Института ботаники АН УССР. Role of the eminent scientists V.I. Lipsky and O.V. Fomin in the development of scientific backgrounds for establishing the Botanical Garden of the Ukrainian Academy of Sciences (now M.M. Grysh ko National Botanical Garden, NAS of Ukraine) is highlighted. History of the Botanical Garden from 1935 to 1944 within the Institute of Botany is described.